Doctrine for Orders and Decentralization in the British and German Armies, 1885–1935. (November 2015) - Samuels, Martin
Drawing on theories of problems in warfare being 'tame' or 'wicked', this article explores continuity and changes in British and German doctrine through examination of wording, emphasis, and approach in field service manuals. This reveals significant continuities in German doctrine, especially the emphasis on initiative, but growing focus on rapid decision-making, coupled with forward command, to achieve surprise. British doctrine also displayed continuity, focused on controlling the battle and reluctance to allow subordinates to exercise initiative. A shift in British doctrine, from one similar to the German model towards a more restrictive approach, is identified between 1905 and 1909.